Continued Suspense : EC-Hormones and WTO Disciplines on Discrimination and Domestic Regulation: Appellate Body Reports: Canada/United States--Continued Suspension of Obligations in the EC-Hormones Dispute, WT/DS320/AB/R,WT/DS321/AB/R, Adopted 14 November 2008 - Hoekman, Bernard (2012)
Based on the reasoning of the Appellate Body in Canada/United States--Continued Suspension of Obligations in the EC-Hormones Dispute ('Continued Suspension'), this paper analyzes the distinction between the national-treatment obligation under Article III of GATT and the requirement under the Agreement on Sanitary and Phytosanitary (SPS) Measures that such measures be based on a risk assessment that takes into account available scientific evidence. The Appellate Body's reasoning makes clear that the primary purpose of the SPS Agreement is to discipline discriminatory regulation, and not the level of protection. We argue that the case clarifies that de facto protection (market segmentation) created by an SPS measure must be motivated by demonstrating that the measure is addressing a market failure, as reflected in the existence of some scientific basis for a health or safety concern. The scientific-basis requirement is a means for determining the intent of an SPS measure. While this is a factor that is ostensibly not relevant in GATT national-treatment cases, the need for scientific justification is not a move away from a concern with preventing illegitimate discrimination against imported products.